Stratified psoriasis treatment plans: why is patient preference information needed?. (31st August 2021) - Gonzalez, J.M.; Reed, S.D.; Johnson, F.R.
Abstract : Linked Article: Dalal et al. Br J Dermatol 2021; 185:978–987 .